Socio-materiality of trust: co-design with a resource limited community organisation. Issue 3 (3rd July 2021) - Clarke, Rachel Elizabeth; Briggs, Jo; Armstrong, Andrea; MacDonald, Alistair; Vines, John; Flynn, Emma; Salt, Karen
ABSTRACT: Trust is an essential if often implicit aspect of co-design particularly when working in community-based, political and sensitive settings. Current co-design literature, however, remains fairly limited focusing on interactions between people as primary agents of trust. Drawing on research conducted with a poverty alleviation charity based in the UK, we illustrate how trust and distrust can also be mediated through material resources used in the co-design process. The paper highlights the significance of materials in negotiating the interdependencies of trust, in how distrust can be leveraged and trust can be supported through sensitive socio-material exchange conducted with resource limited community organisations.